Hubungan Tingkat Pengetahuan Perawat dengan Ketrampilan Melaksanakan Prosedur Tetap Isap Lendir/Suction di Ruang ICU RSUD Prof. Dr. Margono Soekarjo Purwokerto - Paryanti, Sri; Haryati, Welas; Hartati, (Jurnal Keperawatan Soedirman, 2007)
One of nursing interventions that is regularly done by nurses in ICU is airway-suctioning procedure. Prevent infection injury, brancho, spasm, oedema, and airway bleeding as well to the patients. Nurses must carry out this procedure correctly. This study was undertaken to obtain information on the relation of nurse’s knowledge of suctioning with nurse’s suctioning skill in ICU Margono Soekarjo General Hospital. This study was description analysis used cross sectional method. Population was all nurse worked in ICU Margono Soekarjo General Hospital. It recruited 22 nurses out of 25 nurses in ICU selected through inclusive criteria. Rank Spearman correlation and frequency distribution were applied to this study. Statistical test shows there was Rank Spearman correlation coefficient = 0,587 and p value = 0,004. Must nurses had a high category (68,2%) on knowledge of airway suctioning only 4,5 % under low category and 27,3% under moderate category. Nurse’s skill on airway suctioning was 77,3% under good category and the least was 22,7% for sufficient category. However to nurse categorized under bad and less good category. There is statistically significant relation between nurse’s knowledge and nurse’s skill on airway suctioning procedure in ICU Margono Soekarjo General Hospital (p=0,004). Both nurse’s knowledge and nurse’s skill on airway suctioning on ICU nurses are categorized high and good